Position-sensorless control of direct drive permanent magnet synchronous motors for railway traction - Frenzke, Thorsten; Piepenbreier, Bernhard (IEEE PESC 04, 2004)
A procedure for position-sensorless control of permanent magnet synchronous motors with surface mounted magnets is proposed, that is suitable to large traction drives with their restrictions like high inverter-utilisation and low switching frequency. Position and speed are obtained by an observer using a voltage and an inductance motor model together with test signal injection at low speed. Improvements of the basic estimation scheme are presented. The method has been tested successfully in the lab with a 28 kW standard servomotor.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.LEEAS.positi